Pregnancy rate following an estradiol-free fixed- TAI protocol during breeding and non-breeding season in water buffaloes under tropical condi- tions - Adriana Camacho de Gutiérrez; Obdulio Camacho; Steward Fernández; Yerixo González; Juan Carlos Gutiérrez-Añez (Revista Científica)
Fixed-timed artificial insemination (FTAI) protocols combining estradiol (E2) and progesterone (P4) are commonly used in the tropics, with adequate pregnancy rates throughout the year in buffaloes. However, the application of E2 and its related esters in food-producing animals is banned in the European Union and by the FDA-USA. This study aimed to evaluate the pregnancy rate (PR) after FTAI in buffalo cows (Bubalus bubalis) treated during the breeding (September-January) and non-breeding season (February-June) using a protocol based on P4 intravaginal devices (IVD) combined with GnRH and PGF2α. The trial was performed on a commercial buffalo farm in Zulia State, Venezuela. Two hundred forty-seven buffalo cows (1-14 calvings) with a body condition score (BCS) of 3.15 ± 0.39 were selected. Cows were synchronized on a random day of the estrus cycle. To synchronize the ovulation on day 0, a dose of 10.5 μg GnRH-analog (Buserelin benzoate acetate, Gestar®) was injected intramuscularly (IM) plus the insertion of an IVD maintained for nine days [TRIU B®: 1.0 gr P4, (n=139); CIDR®: 1.38 gr P4 (n=77); or PREGNAHEAT-E®: 250 mg of medroxyprogesterone acetate (MPA), (n= 18)]. On day 9, IVD was removed, and 0.50 mg of Cloprostenol (Estrumate®, Intervet, MSD Animal Health) plus 500 IU of eCG (Folligon®, Intervet, MSD Animal Health) were given IM. On day 11, a dose of 10.5 μg GnRH-analog IM was used, and 8-12 hours later, they were artificially inseminated using frozen-thawed semen of bulls with proven fertility. The pregnancy rate (PR) was determined 30-32 days after AI by ultrasound. The data was analyzed by logistic regression through the Proc Logistic, and continuous and linear character variables were analyzed through the Proc GLM of the SAS® package. The overall PR was 52.2% (n = 129/247). Evaluation of independent variables, such as the number of calving and BCS, did not affect the PR (p>0.05). The PR was similar (p>0.05) amongst the reproductive and non-reproductive seasons [52.2%: (66/129) vs. 53.4% (63/118), respectively]. IVD-type did not affect the PR (p>0.05) [TRIU- B®: 52.6% (80/152), CIDR®: 53.3% (41/77) and PREGNAHEAT-E®: 44.4% (8/18)]. In conclusion, this FTAI protocol based on P4 and GnRH and PGF2α produced adequate pregnancy rates during breeding and non-breeding seasons. These findings suggest that GnRH could be considered to substitute E2 esters in the P4-based FTAI protocols in water buffaloes under tropical conditions.